2018
DOI: 10.1002/lipd.12014
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of Lipoprotein Receptors Is Increased in the Infarcted Area After Myocardial Infarction Induced in Rats With Cardiac Dysfunction

Abstract: Left ventricular (LV) remodeling after myocardial infarction constitutes the structural basis for ventricular dysfunction and heart failure. The characterization underlying the expression of lipoprotein receptors in cardiac dysfunction is scarcely explored. The aim of this study was to analyze the status of lipoprotein receptors on the infarcted and noninfarcted areas of LV and to verify whether nanoparticles that mimic the lipid structure of low-density lipoprotein (LDL) and have the ability to bind to LDL re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…Distinct elevations in LVMI were reported in the MI group in a previous study, which was consistent with the observations of our study 22 . Furthermore, upregulated α-SMA and PCNA have been identified in the infarcted area of MI,23, 24 which was also in line with our study. In vivo experiments in this study revealed decreased levels of miR-494, VEGF, and FGF, but increased levels of LRG1, Wnt-1, and β-catenin in myocardial tissues of MI rats.…”
Section: Discussionsupporting
confidence: 93%
“…Distinct elevations in LVMI were reported in the MI group in a previous study, which was consistent with the observations of our study 22 . Furthermore, upregulated α-SMA and PCNA have been identified in the infarcted area of MI,23, 24 which was also in line with our study. In vivo experiments in this study revealed decreased levels of miR-494, VEGF, and FGF, but increased levels of LRG1, Wnt-1, and β-catenin in myocardial tissues of MI rats.…”
Section: Discussionsupporting
confidence: 93%
“…The significance of these finding, however, awaits further investigation. Enhanced expression of SR-BI, specifically in the infarcted area, has recently been reported in rats subjected to myocardial infarction induced by left coronary ligation, plausibly suggesting a role of SR-BI in myocardial repair ( 63 ). At a cellular level, SR-BI mediated the cardioprotective effects of HDL against necrosis induced by oxygen and glucose deprivation in neonatal mouse and human cardiomyocytes ( 64 ).…”
Section: Discussionmentioning
confidence: 88%
“…In neoplastic or inflamed tissues, upregulation of LDL receptors occurs, which allows internalization into cells of drugs carried in LDE at much higher amounts compared with the commercial presentation of these drugs (27). In several animal models, drugs carried in LDE showed increased therapeutic efficacy together with a drastic reduction in toxicity (28)(29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%
“…than conventional MTX (28). LDEMTX was successfully tested in several animal models of diseases with an important inflammatory component, such as atherosclerosis, rheumatoid arthritis, myocardial infarction, and heart transplantation (29)(30)(31)(32). In those animal models, LDEMTX showed antiinflammatory action much greater than conventional MTX.…”
Section: Introductionmentioning
confidence: 99%